Batho Pele revitalisation programme and service delivery in the public service. - Motalane, Kebeile Veronica (My University, 2014)
ABSTRACT The introduction of the Batho Pele (BP) White Paper in 1997 sought to provide a policy framework and practical strategy aimed at improving access to public services towards an efficient, effective and development oriented Public Service. The study aimed at exploring the extent to which the Public Service; in particular the Department of Public Service and Administration referred to in this study as “the DPSA”, has implemented the Batho Pele principle of Redress. Batho Pele (Sesotho word for People First) aspires to portray the public service as government machinery that is citizen-oriented, informed by the eight principles of Consultation, Access, Service Standards, Courtesy, Information, Openness and Transparency, Redress and Value for Money. The challenges highlighted by this study demonstrated that the mechanisms and measures put in place in support of the implementation; monitoring and feedback of the Batho Pele; in particular the principle of “Redress”; as a focus of this study; are not yet responsive to complaints handling processes and procedures in dealing with citizens’ dissatisfactions when interfacing with government during the delivery of services. Literature review and the empirical evidence in the study demonstrated the need for managers to view complaints and demands for redress by beneficiaries as valuable learning opportunities to come up with preventative and corrective measures to service delivery problems within the public service. The Redress procedures and systems which are critical for fairness, courtesy, openness and transparency and sustainability still need to be designed better; well co-ordinated and collaborated to ensure sustainable implementation of complaints handling mechanisms and system within the public service. This would include formal recognition for beneficiaries, their right to information about government decision-making and spending patterns, and rights to seek redress for poor-quality service delivery. The methodology and the findings of the study with the DPSA as a focus area, highlighted the following as critical ingredients towards sustainable implementation, monitoring and feedback of the “redress principle”, within the public service.
MM 2014
Keywords: Public administration,Civil service reform,Management.